Pengaruh Brand Ambassador Terhadap Keputusan Pembelian Melalui Social Media Marketing Sebagai Variabel Intervening : Studi Kasus Konsumen Produk Nature Republic Di Kota Malang - Hasna Hamida Alifia Ar-Rasyi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Brand Ambassador and Social Media Marketing are effective marketing strategies to encourage purchasing decisions. This study aims to determine the direct and indirect effects of brand ambassadors and social media marketing on purchasing decisions for Nature Republik products. This research uses a quantitative descriptive approach. The population of this study were consumers of Nature Republik, the sampling technique used purposive sampling totaling 100 respondents who live in Malang City. This research data analysis was carried out using the SEM PLS method using the SmartPLS application, descriptive analysis test and hypothesis testing. The results showed that 1) Brand Ambassador has a positive and significant effect on purchasing decisions for Nature Republic products in Malang City, 2) Brand Ambassador has a positive and significant effect on Social Media Promotion of Nature Republic products in Malang City, 3) Social Media Promotion has a positive and significant effect on Purchasing Decisions for Nature Republic products in Malang City.